The effect of corporate governance, financial distress, tax incentives, and firm size on accounting conservatism in the Indonesia banking sectors - Aulia, Afra; Praptiningsih, Praptiningsih (WIM Solusi Prima, 2025)
The objective of this study is to examine the effect of corporate governance, financial distress, tax incentives, and firm size on accounting conservatism in the banking sector in Indonesia. Corporate governance mechanisms in this study are represented by managerial ownership and institutional ownership, reflecting the role of governance structures in influencing accounting practices. The study analyzes a total of 75 data units derived from 25 banking companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2023 period, selected through purposive sampling. This research employs a quantitative research method and relies on secondary data sources, such as annual reports and company financial statements. The analysis technique used is multiple linear regression technique using Stata version 13. The results of the study prove that there is a negative significant effect of financial distress and tax incentives, but there is no significant effect of managerial ownership, institutional ownership, bank size on accounting conservatism.